Effectiveness Of Virtual Reality On Post-Amputation Pain Lower Extremities : Literatur Review - Muthia, Ellen; Masfuri, Masfuri; Yulia, Yulia (JURNAL CITRA KEPERAWATAN, 2024)
Amputation of the lower extremities not only causes physical loss and psychological disturbance but also leads to discomfort and continuous pain sensation. Virtual reality is one of the promising alternatives as a non-pharmacological intervention in reducing pain. This method provides an experience in virtual activity that can distract patients from pain and increase relaxation. The purpose of this writing is to help identify the effectiveness of virtual reality in reducing post-amputation pain in the lower extremities. The method used in this article is a literature review method. Article searches were conducted on Scopus, Sage, Google Scholar, and ProQuest websites by entering the keywords "virtual reality pain amputation lower extremity". There were 10 articles used after being selected using these keywords. Virtual reality shows the potential effectiveness in reducing pain and improving functional outcomes in patients with lower extremity amputations. Virtual reality training oriented towards tasks also focuses on improving motor function and reducing avoidance behavior by providing a safe and controlled environment for individuals to practice and gradually increase their mobility.